International migration and its contribution in the transmission of malaria in the Zimbabwean border districts. - Chiruvu, Roy; Matare, Takura; Nmehielle, Nkechi-Obisie-; Gombe, Notion T; Mhlanga, Maxwell; Ndaimani, Augustine (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Objective: This study aimed to provide evidence for policy and programming on malaria in Zimbabwe and othersub-Saharan countries. It also aimed to provide insight on how best to improve cross border collaborations inthe prevention and control of malaria. Design and setting: A cross sectional mixed methods study design usingboth quantitative and qualitative approaches was conducted from February to April 2016 in the selected healthfacilities in Mutare and Mutasa districts of Zimbabwe. Quantitative methods included record review ofadministrative registers from 2012 to 2015 in the participating health facilities in the border districts of Mutasaand Mutare. Data on malaria test, the result of the malaria tests and sociodemographic data were abstracted fromthe register. Qualitative methods comprised of focus group discussions (FGDs) with the health centre committeemembers, patients (both sexes in one FGD) in the health facilities. A sample of 318 patient records was selectedthrough purposive sampling.Univariate and bivariate analysis were done using Epi Info 7. Thematic analysiswas employed in the analysis of qualitative data. Main outcome: The main outcome measure was the level ofmalaria attributable to international migration. Results: The proportion of malaria cases from Mozambiquetreated in Zimbabwe rose from 2.7% in 2013 to 5.1% in 2015. Males constituted 60% of patients fromMozambique and 75.5% of the patients aged from 5-34 years. Older children (12-59 months) were moresusceptible to infections compared to younger ones. Being male (OR 1.29, 95% C.I 1.12-1.42) and being lessthan 5 years (OR 1.23 95%C.I 1.10-1.38) were significant risk factors for malaria transmission in Mutasa andMutare. Participants in FGDs cited climate change as the main cause of an increase in malaria transmission.Other factors cited include resistance to indoor residual spraying; ineffective chemicals; poor diagnosis andinsufficient drugs. Conclusions: The study revealed that international migration is a significant contributor tomalaria transmission across bordering districts in Zimbabwe. It is imperative that the sub-Saharan governmentsintensify collaborative malaria prevention and control action and strategies. There is great need for continuousentomological surveillance to ensure that the different interventions across the countries are effectively managedthrough an evidence based approach.